Epidemiology and Clinical Features of Methicillin-Resistant Staphylococcus aureus in the University Hospital, Jeddah, Saudi Arabia - Tariq A Madani (Canadian Journal of Infectious Diseases)
OBJECTIVE: To describe the prevalence, demography and clinical characteristics of patients who were colonized or infected with methicillin-resistant Staphylococcus aureus (MRSA) in 1998 at King Abdulaziz University Hospital, Jeddah, Saudi Arabia.